The world through the prism of language: social context and cognitive patterns in gender and classifiers - Aikhenvald, Alexandra Y. (Revista Brasileira de Linguística Antropológica, 2025)
Semantic categorization of nouns — which is reflected in gender and classifiers — relates to cultural conventions and environment. We also address the correlations between the use of classifiers and newly introduced cultural practices. The meanings of gender may have additional overtones of social value. Gender — particularly as it is assigned to humans — is prone to reflect the stereotypes associated with social gender — the societal implications and norms associated with being a man, or a woman, or a representative of further, gay, transgender, and other groups. Similarly, the use of a numeral classifier referring to humans may correlate with social gender, mirroring the woman’s place in society and social changes. Numeral classifiers for humans in languages of East and South-east Asia reflect the societal organization. Highly specific classifiers reflect environmental traits and people’s ways of life. Semantic features encoded in gender and classifiers offer a unique insight into the human mind, and reflect perceptual and cognitive mechanisms shared by humans.